The role of cardiac power and lactate clearance as an indicator of resuscitation success among pediatric patients with shock in the intensive care unit of Cipto Mangunkusumo Hospital - Irene Yuniar; Reni Fitriasari; Yogi Prawira; Setyo Handryastuti; Muzal Kadim; Silvia Triratna; Mulyadi M. Djer (BMC, 2023)
Abstract Background Shock in children remains the primary cause of mortality and morbidity worldwide. Furthermore, its management outcome is improved using many hemodynamic parameters, such as cardiac power (CP) and lactate clearance (LC). Cardiac power is a contractility index based on the measurement of flow and pressure, and it is a relatively new hemodynamic parameter with limited studies. In contrast, LC has been proven useful as a target outcome in shock resuscitation. This study aims to explore the values of CP and LC in pediatric shock and their association with clinical outcomes. Methods This prospective observational study was conducted on children (1 month-18 years old) with shock at Cipto Mangunkusumo Hospital, Indonesia, from April to October 2021. We measured CP using ultrasonic cardiac output monitoring (USCOM®) and serum lactate levels at 0, 1, 6, and 24 h post-initial resuscitation. Subsequently, the variables were described and analyzed with the resuscitation success, length of stay, and mortality. Results A total of 44 children were analyzed. There were 27 (61.4%), 7 (15.9%), 4 (9.1%), 4 (9.1%), and 2 (4.5%) cases of septic, hypovolemic, cardiogenic, distributive, and obstructive shock, respectively. Within the first 24 h post-initial resuscitation, CP and LC had an increasing trend. Compared to children who had successful resuscitation, those who did not have successful resuscitation had similar CP at all time points (p > 0.05) and lower LC at 1 and 24 h post-initial resuscitation (p < 0.05). Lactate clearance was an acceptable predictor of resuscitation success (area under the curve: 0.795 [95% CI: 0.660-0.931]). An LC of 7.5% had a sensitivity, specificity, positive predictive value, and negative predictive value of 75.00%, 87.5%, 96.43%, and 43.75%, respectively. Lactate clearance in the first hour post-initial resuscitation had a weak correlation (r=-0.362, p < 0.05) with hospital length of stay. We found no difference in CP and LC among survivors compared to nonsurvivors. Conclusions We found no evidence that CP was associated with resuscitation success, length of stay, or mortality. Meanwhile, higher LC was associated with successful resuscitation and shorter length of stay at the hospital, but not mortality.